Proceedings of the International Symposium on Social Sciences, Education, and Humanities (ISSEH 2018) 2019
DOI: 10.2991/isseh-18.2019.27
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Ecotourism Development in Tasikmalaya District, West Java

Abstract: The Tourism Sector in Tasikmalaya Regency has excellent potential to be developed towards ecotourism-based tourism areas. Mount Galunggung Tourism Area, Jasper Park Area and Kampung Naga Region are the three tourism areas that are most likely to be used as ecotourism area modeling. The objectives of this study are: identify the level of fulfillment of ecotourism criteria in the Galunggung Mountain Tourism Area, Jasper Park, and Kampung Naga; and formulate the development and modeling of ecotourism in the touri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…7. Tourism Function Tourism is everything related to tourism, including the exploitation of tourist objects and attractions and related businesses in that field [19]. The tourism potential of Ten Thousand Hills cannot be separated from the condition of geodiversity which has its own uniqueness.…”
Section: Hydrological Function From the Hydrological Point Of View Th...mentioning
confidence: 99%
“…7. Tourism Function Tourism is everything related to tourism, including the exploitation of tourist objects and attractions and related businesses in that field [19]. The tourism potential of Ten Thousand Hills cannot be separated from the condition of geodiversity which has its own uniqueness.…”
Section: Hydrological Function From the Hydrological Point Of View Th...mentioning
confidence: 99%
“…Pertama, diwakili oleh sumber daya manusia atau "bakat karyawan" dalam suatu organisasi, yang mencakup sejauh mana anggota memiliki keterampilan dan motivasi yang dibutuhkan untuk melakukan pekerjaan secara efektif (Ratnasari, 2019). Sebagai alternatif, beberapa peneliti menganggap modal manusia sebagai indikasi tindakan kerja berkinerja tinggi (Pakpahan, 2020), filosofi perusahaan yang mempengaruhi bakat (Alimudin, 2019), atau komitmen organisasi kepada karyawan yang mempengaruhi hasil di perusahaan level (Fadjarajani, 2019). Misalnya, Alimudin (2019) berpendapat bahwa sumber daya manusia mencerminkan pengetahuan dan keterampilan yang melekat pada diri manusia.…”
Section: Pendahuluanunclassified
“…Until now, Galunggung Mountain has become an interesting tourist destination. Fadjarajani et al (2019) reported number of both local and foreign tourists to reach hundreds and thousands of people per year. One of the points of interest in this area is Mt.…”
Section: Introductionmentioning
confidence: 99%